Does cultural resource endowment backfire? Evidence from China’s cultural resource curse - Zhou, Jianxin; Xia, Zhen; Lao, Yongshi (Frontiers in Psychology, 2023)
Resource curse theory suggests that regions rich in natural resource endowments accumulate adverse economic competitive, but few studies have focused on causes and mechanisms of cultural resource curses. Since the development of the cultural industries is relatively backward in some regions with rich cultural resources in central and western China. Combined with the theory of cultural resources and the resource curse, we build cultural resource endowment and cultural resource curse coefficients and measure the distribution of cultural resource curses based on the dataset of 29 provinces in China covering 2000-2019. The results show that there is a serious cultural resource curse in western China. The causes of the cultural resource curse are multiple, place attachment and cultural field can influence cultural behaviors, and the environmental impact of industrial ecosystems causes path dependence in cultural resource exploration and cultural industry development. We further empirically tested the influence of cultural resources on cultural industries in different sub-regions of China and the transmission mechanism of the curse of cultural resources in western China. The results show that the influence of cultural resources on the cultural industries is not significant in the overall of China, but it is significantly negative in western China. The resource-dependent model of cultural industries development in western China has attracted more primary labor and crowded out government spending on education. Moreover, it hinders the upgrading of human resources and inhibits the modern innovative development of the cultural industries. This is an important reason for the curse of cultural resources in the development of cultural industries in western China.